Predictors of hepatocellular carcinoma recurrence associated with the use of direct‐acting antiviral agent therapy for hepatitis C virus after curative treatment: A prospective multicenter cohort study. (22nd March 2019) - Nakano, Masahito; Koga, Hironori; Ide, Tatsuya; Kuromatsu, Ryoko; Hashimoto, Satoru; Yatsuhashi, Hiroshi; Seike, Masataka; Higuchi, Nobito; Nakamuta, Makoto; Shakado, Satoshi; Sakisaka, Shotaro; Miuma, Satoshi; et al.
Abstract: Background: Previous studies have suggested an association between the use of direct‐acting antiviral agents (DAAs) for treating hepatitis C virus (HCV) infection and the resulting decrease in the incidence of hepatocellular carcinoma (HCC); however, it is unclear whether DAAs prevent the recurrence of HCC after curative treatment for HCC. This study aimed to prospectively investigate HCC recurrence and its predictors after curative treatment for HCC. Methods: A total of 3012 patients with chronic HCV infection, with or without cirrhosis, who were treated with DAAs were enrolled between January 1, 2015 and January 31, 2017 as per the institutional review board approved study protocol at 15 institutions, including 10 university hospitals and five high‐volume centers in the Kyusyu area of Japan. Of the 3012 patients, 459 patients who had HCC but were cured with surgery or ablation therapy (curative treatment) before the use of DAAs were included in the analysis. Results: During a mean follow‐up period of 29.4 months, 217 (47.2%) patients developed HCC recurrence. The median time to recurrence was 34.0 months, and the 1‐, 2‐, and 3‐year cumulative HCC recurrence rates were 27.1%, 43.4%, and 50.8%, respectively. The risk factors for HCC recurrence were the α‐fetoprotein (AFP) level before DAA therapy ( P  = 0.0047) and the number of curative treatments for HCC before DAA therapy ( P  < 0.0001). Conclusions: A high AFP level and multiple occurrences of HCC before DAA therapy are associated with a high risk for HCC recurrence after curative treatment. Follow‐up after DAA therapy should include special attention to the abovementioned risk factors. Abstract : HCC recurred in 47.2% (217/459) of patients with precured HCV‐related HCC, who achieved SVR12 by DAA therapy, during a long mean follow‐up period of 29.4 months in this prospective study. High AFP level and multiple occurrences of HCC before DAA therapy were significant risk factors for the recurrence.